The Management of the Tahfidz al-Qur’an Flagship Program: Strengthening Qur’anic Literacy at MI Taufiqiyah Semarang - Lailiyah Novi Nuri Maziliana; Zulaikhah; Nur Asiyah; Abdulghoni Lateh (AJIS: Academic Journal of Islamic Studies, 2025)
This study aims to analyze the management of the flagship tahfidz al-Qur’an program in strengthening Qur’anic literacy at MI Taufiqiyah Semarang. The research employs a qualitative approach with a case study design, utilizing interviews, observations, and documentation as data collection techniques. Data were analyzed using the interactive model of Miles and Huberman, which consists of data reduction, data display, and conclusion drawing, while validity was ensured through source and technique triangulation. The findings indicate that the strengthening of Qur’anic literacy is not solely determined by the tahfidz instructional method, but rather by the consistent implementation of management functions, including needs-based planning, competency-based organizing, gradual instructional implementation, and tiered as well as continuous evaluation. This managerial system contributes to improving students’ Qur’anic literacy quality, particularly in terms of reading fluency, accuracy of makhraj (articulation points), and the habituation of muroja’ah (systematic review). Theoretically, this study contributes by proposing an empirical model of tahfidz program management grounded in Qur’anic literacy at the Madrasah Ibtidaiyah level, thereby extending the discourse of Islamic educational management from a predominantly administrative orientation toward strengthening religious literacy outcomes.